Vulvodynia, "A Really Great Torturer": A Mixed Methods Pilot Study Examining Pain Experiences and Drug/Non-drug Pain Relief Strategies. Issue 8 (13th June 2019) - Schlaeger, Judith M.; Pauls, Heather A.; Powell-Roach, Keesha L.; Thornton, Patrick D.; Hartmann, Dee; Suarez, Marie L.; Kobak, William H.; Hughes, Tonda L.; Steffen, Alana D.; Patil, Crystal L.
Abstract: Background: Women with vulvodynia, a chronic pain condition, experience vulvar pain and dyspareunia. Few studies examine the range and combination of treatment strategies that women are actually using to reduce vulvodynia. Aim: To describe pain experiences and pain relief strategies of women with vulvodynia. Methods: Convenience sample, 60 women with vulvodynia (median age 32.5 [interquartile range IQR 8.5] years; 50 white, 10 racial/ethnic minorities) completed PAIN Report It and reported use of drugs and alcohol and responded to open-ended questions. Univariate descriptive statistics and bivariate inferential tests were used to describe average pain intensity scores, alcohol use, smoking, number of pain relief strategies, and their associations. Women's open-ended responses about their pain experiences and drug and non-drug pain relief strategies (NDPRS) were analyzed for patterns. Outcomes: Our mixed methods analysis connected data from pain measures, prescribed treatments and self-reported behaviors with women's free responses. This enabled nuanced insights into women's vulvodynia pain experiences. Results: Women's descriptions of their pain and suffering aligned with their reported severe pain and attempts to control their pain, with a median pain intensity of 6.7 (IQR 2.0) despite use of adjuvant drugs (median 2.0 [IQR 2.0]), and opioids (median 1.0 [IQR 2.0]). 36 women (60%) used alcohol to lessen their pain. 26 women (43%) listed combining analgesics and alcohol to relieve their pain. 30 women (50%) smoked cigarettes. 54 women (90%) used ≥1 NDPRS. The mean number of NDPRS used was 2.1 ± 1.3 (range 0–6). The 5 most common NDPRS from women's comments were herbal medicine (40%), acupuncture (27%), massage (22%), hypnosis (15%), and mental healthcare (13%). Clinical Implications: Severe pain in women with vulvodynia may be a clinical indicator of those at higher risk of combining prescription pain medications with alcohol, which are all central nervous system depressants and may potentiate overdose. Strengths and Limitations: This pilot study demonstrated that the mixed methods approach to help understand the complexity of vulvodynia was feasible. We identified data showing a reliance on a high-risk mix of prescriptions and alcohol to reduce vulvodynia pain and a high prevalence of cigarette smoking. However, as a pilot study, these results are considered preliminary; the sample may not be representative. Perhaps only women at the extreme end of the pain continuum participated, or women took the survey twice because identifiers were not collected. Conclusion: Despite attempts to reduce pain using multiple therapies, including alcohol, women's vulvodynia pain is severe and not controlled.